Effects of Growth and Volatility in Public Expenditures on Economic Growth: Theory and Evidence. - Liutang Gong; Heng-fu Zou (Annals of Economics and Finance, 2002)
This paper sets up a theoretical model linking the growth rate of the economy to the growth rate and volatility of different government expenditures. On a theoretical basis, it is found that volatility in government spending can be positively or negatively associated with economic growth depending on the intertemporal elasticity in consumption. On an empirical basis, it is rather surprising to find no association between growth in capital expenditure and output growth, whereas growth in current expenditure seems to stimulate output growth. In particular, growth in transportation and communication seems to have a negative effect on output growth. It is also very interesting to find that the rises in the volatility in the growth of general public services, transportation, and communication have a positive effect on output growth.